2021
DOI: 10.3390/w14010068
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Benefits and Ecosystem Services Provided by Green Roofs—A Review

Abstract: Water-sensitive urban design (WSUD) has been widely used in cities to mitigate the negative consequences of urbanization and climate change. One of the WSUD strategies that is becoming popular is green roofs (GR) which offer a wide range of ecosystem services. Research on this WSUD strategy has been continuously increasing in terms of both quantity and quality. This paper presents a comprehensive review quantifying the benefits of GRs in papers published since 2010. More precisely, this review aims to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 122 publications
1
8
0
1
Order By: Relevance
“…The trend shows a constant pattern, where smaller-scale structures were more common than a large-scale study. This result is also similar to that of another review study that focused only on GR [50]. A case study regarding GW in Hong Kong showed that a 100% The subcategory distribution of UGI types is illustrated in Figure 10b.…”
Section: Scale and Height Parameterssupporting
confidence: 86%
“…The trend shows a constant pattern, where smaller-scale structures were more common than a large-scale study. This result is also similar to that of another review study that focused only on GR [50]. A case study regarding GW in Hong Kong showed that a 100% The subcategory distribution of UGI types is illustrated in Figure 10b.…”
Section: Scale and Height Parameterssupporting
confidence: 86%
“…The fact that green roofs are dynamic as regards biomass, plant height and cover, moving over time, is well documented in scientific literature [ 16 , 65 , 66 ]. It is also worth noting that two-dimensional plant ground cover in green roofs is important in terms of visual attractiveness and other ecosystems services [ 67 , 68 ]. As reported by some authors, although the simultaneous presence of species and different growth shapes contributes to maximizing the provision of services on a green roof (reduction of substrate surface temperature, rainfall retention etc.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of GRs has been increasing in the last two decades due to a considerable number of global efforts [9]. An imbalanced research focus with regards to GR benefits has been reported in the literature with the greatest attention towards runoff and temperature reductions [10][11][12]. GR studies have been mostly conducted in the USA and many European countries, which result in the insufficient awareness of GR potential in other countries.…”
Section: Introductionmentioning
confidence: 99%